Imam Farahi’s view on rationality: a framework for modernity discourse - Ghazi, Muhiuddin; Ali, Mohammed Farid; Haider, Zulqernain; Idris, Fathiyyatunnur (IIUM Press, International Islamic University Malaysia, 2018)
Imam Hamiduddin Farahi (d. 1930) is one of the legendary Islamic scholar, philosopher, theologian and exegetist of the Quran of the modern era. His works cover reconceptualization and reactivation of the idea of coherence in the Quran, redefining all Islamic sciences and disciplines which have been regarded as necessary to understand the Quran or which have originated from the Quran giving the centrality and discernment to the Quran. He challenged many of the prevailing discourses in the field of Quranic sciences, sciences of hadith, jurisprudence and its principles, logic, theology and philosophy, and field of Arabic grammar and rhetoric. This paper aims to study his thoughts on the role of reason in the Islam and how Islam nurtures and trains the reason in its own way. To achieve this aim, his book on the science of the argument of the Quran namely, Hijaj-ul-Quran in addition to few other books on the same topic is consulted by employing content analysis methodology. The findings show that the discussion of compatibility of reason with revelation is the result of misunderstanding the latter two. As a matter of fact, reason and revelation goes together complementing each other and there is no possibility of any kind of contradiction between the two. The Quran not only encourages the use of reason, rather it provides some rules and mechanism to further develop the ability of reasoning to a higher altitude which is not easily attainable without painstaking effort and long exercise.